The Effect of Recombinant DNA Technology in Medicine - Haowa Mohammed Madi; Aiada Daw Mohamed (African Journal of Advanced Pure and Applied Sciences, 2023)
Recombinant DNA is a form of artificial DNA that is made through the combination of one or more DNA strands, this technology offered new projections for improvements in a wide range of therapeutic products with immediate effect in medicine. Recombinant DNA technology has been effectively used in health care to produce numerous human proteins in microorganisms, such a protein is beneficial for treating diseases like human insulin, vaccine production and hormones. also, with this technology, treatment strategies are improved by developing diagnostic kits, monitoring devices, and new therapeutic approaches. The synthesis of human insulin and erythropoietin by genetically modified bacteria and the production of new types of experimental mutant mice for research purposes is one of the leading examples of genetic engineering in health. This review introduces the main steps of recombinant DNA technology and various classes of therapeutic products that are produced using recombinant DNA technology.